2016
DOI: 10.2174/1570163813666160905115325
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Phytotherapeutic Aspects of Elaeagnus angustifolia L.

Abstract: Persian or Russian olive (Elaeagnus angustifolia L.), from the family Elaeagnaceae, is a nitrogen-fixing thorny shrub extensively used in traditional medicine to alleviate pain and treat rheumatoid arthritis, osteoarthritis, gastrointestinal problems, fever, and asthma. The current review has tried to give a concise overview of the phytochemistry and pharmacological properties of the plant from published data. Accordingly, published English literatures on Elaeagnus angustifolia were gathered from popular datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…We report that EA plant extract can suppress cell proliferation, as well as dysregulate cell-cycle progression of SKBR3 and ZR75-1 cells, along with induction of RELT and inhibition of colony formation in both cell lines. EA plant is known for its antioxidant characteristics and has been used conventionally for the treatment of several diseases and inflammation [ 16 , 20 , 21 ]. Moreover, EA consists of bioactive compounds (flavonoids and neoclerodane diterpenoids), which can play a role in promoting apoptosis and cell-cycle progression, as well as inhibiting angiogenesis and EMT events, thus potentially preventing cancer development and progression [ 12 , 13 , 16 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report that EA plant extract can suppress cell proliferation, as well as dysregulate cell-cycle progression of SKBR3 and ZR75-1 cells, along with induction of RELT and inhibition of colony formation in both cell lines. EA plant is known for its antioxidant characteristics and has been used conventionally for the treatment of several diseases and inflammation [ 16 , 20 , 21 ]. Moreover, EA consists of bioactive compounds (flavonoids and neoclerodane diterpenoids), which can play a role in promoting apoptosis and cell-cycle progression, as well as inhibiting angiogenesis and EMT events, thus potentially preventing cancer development and progression [ 12 , 13 , 16 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elaeagnus angustifolia ( EA ), commonly known as wild olive, oleaster, silver berry, or Russian olive [ 11 , 15 ], is a deciduous tree belonging to the family of Elaeagnacea (Araliaceae) widely distributed in the Middle East, as well as Mediterranean regions [ 12 , 16 ]. EA fruit is highly nutritious and contains vitamins (vitamin C, tocopherol, thiamine B1, and carotene), sugar, proteins, and several minerals, like potassium, iron, magnesium, and calcium [ 17 , 18 , 19 ]; the leaves and flower extract are rich in secondary metabolites such as coumarins, phenolcarboxylic acids, flavonoids, saponins, and tannins [ 16 , 20 , 21 ]. Previous studies have shown that EA exhibits anticancer effects as a result of its essential oils (ethyl cinnamate, 2-phenyl-ethyl benzoate, 2-phenyl-ethyl isovalerate, nerolidole, squalene, and acetaphenone), flavonoids (quercetin), and pro anthocyanosides [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, six studies investigated the plants that were reported to have no teratogenic and abortive effects. In some of the articles published in reliable databases, certain plants such as Elaeagnus angustifolia L. 21 , Peganum harmala L. 22 , and Carthamus tinctorius L. 23 were reported to exert teratogenic effects and some other plants such as Peganum harmala L. 24,25 and saffron 25,26 demonstrated to cause abortive effects. However, a few number of studies were conducted mainly to investigate the effects of these plants and their derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Of note is the narrow-leaved olive Elaeagnus angustifolia L. Thus, Iranian researchers have proven the effectiveness of aqueous extract of olive fruit in the treatment of osteoarthritis [4,5]. Scientists from the Tehran University of Medical Sciences have described the cardioprotective, antioxidant, analgesic, antitumor, and anti-inflammatory effects of olive extracts [6]. These data are confirmed by studies of a team of American and Iranian scientists [7].…”
Section: актуальные вопросы фармацевтической и медицинской науки и практики 2021 т 14 № 2(36) с 179-184mentioning
confidence: 88%